Dysphonia and dysphagia consequences of paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS). (September 2021) - Halfpenny, Rhiannon; Stewart, Alexandra; Carter, Alison; Wyatt, Michelle; Jephson, Christopher; O'Dwyer, Emma; Cavalli, Lesley
Abstract: Importance: Paediatric inflammatory multisystem syndrome, temporally associated with SARS-CoV-2 (PIMS-TS) is a novel disease first identified in 2020. Recent cohort studies have described the complex presentation and symptomatology. This paper provides detailed description of the dysphagia and dysphonia symptoms, management, and outcome. Objective: To describe dysphagia and dysphonia in PIMS-TS. Design: Retrospective cohort study. Setting: Single tertiary and quaternary children's hospital. Participants: All 50 children treated for paediatric multisystem inflammatory disease between April and June 2020 were included in this study. Main Outcome(s) and Measure(s): Dysphonia: GRBAS Perceptual Severity Scores, Vocal Handicap Index scores and the Vocal Tract Discomfort Scale. Dysphagia: Functional Oral Intake Scale. Results: Fifty children met the diagnostic criteria for PIMS-TS. 33 (66%) were male. Median age was 10 years (range: 1–17). 36 (72%) were of Black, Asian or minority ethnic background. Nine (18%) required specialist assessment and management of dysphagia and/or dysphonia. Five (55%) were male with a median age of 9 years 7 months (range: 1–15 years). Symptoms typically resolved within three months. Two children presented with persisting dysphonia three months post-presentation. Neurological, inflammatory, and iatrogenic causes of dysphagia and dysphonia were identified. Conclusions and Relevance: Dysphonia and dysphagia are present in children with PIMS-TS. Further data is required to understand pathophysiology, estimate incidence, and determine prognostic factors. This preliminary data highlights the need for dysphagia and dysphonia screening and timely referral for specialist, multidisciplinary assessment and treatment to ensure short-term aspiration risk is managed and long-term, functional outcomes are optimised. Highlights: How does dysphagia and dysphonia manifest in children with PIMS-TS? 50 children, 9 (18%) presented with dysphagia and/or dysphonia requiring specialist assessment and management. Resolution of symptoms occurred in all but 2 cases within 3 months with specialist, multi-disciplinary intervention. Screening for dysphonia and dysphagia in children with PIMS-TS should be conducted to optimise functional outcome.